The global threat of terrorism - Brainard, Jason (Hot topics (Lucent Press), 2020)
Explores the global threat of terrorism today, discussing the rise of terrorism, its costs and effects, and how to handle this threat in the future. Includes color photographs, discussion questions, organizations to contact, quotes, and further reading.